2016
DOI: 10.3390/su8050501
|View full text |Cite
|
Sign up to set email alerts
|

Using Envision to Assess the Sustainability of Groundwater Infrastructure: A Case Study of the Twin Oaks Aquifer Storage and Recovery Project

Abstract: Abstract:The ISI (Institute for Sustainable Infrastructure) Envision rating system is designed to be a comprehensive sustainability assessment that can be applied to a wide range of infrastructure projects, including water supply. With water supply resiliency, a prominent concern in many arid and semi-arid regions, the implementation of a water sustainability metric would be beneficial to both regulators and planners. This review seeks to assess the merit of applying Envision to water infrastructure projects s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Similar to their second conclusion, Saville, Miller, and Brumbelow (2016) also concluded that Envision has a project oriented focus and generally neglects a systems-level perspective.…”
Section: The Project Focus Omits a Systems Scalesupporting
confidence: 60%
See 1 more Smart Citation
“…Similar to their second conclusion, Saville, Miller, and Brumbelow (2016) also concluded that Envision has a project oriented focus and generally neglects a systems-level perspective.…”
Section: The Project Focus Omits a Systems Scalesupporting
confidence: 60%
“…The Envision criteria are multi-disciplinary. Saville, Miller, and Brumbelow (2016) found that environmental sustainability is the focus of 57% of Envision points, contending that while the economic pillar is often the focus of EAs, the social environment should be weighted more heavily in the Envision criteria. While the natural environment is definitely the focus of many criteria, the criteria generally are designed to be interconnected and support various aspects of social, economic and environmental sustainability.…”
Section: There Is An Uneven Weighting Of the Three Sustainability Pillarsmentioning
confidence: 99%
“…Furthermore, while some criteria may be over-weighted relative to local sustainability priorities, others will be under-weighted, so the weighting should balance out. So while Saville, Miller, and Brumbelow (2016) are correct in the finding, their critique is overstated based on this study.…”
Section: There Is No Weighting Of Criteria Based Upon Local Needsmentioning
confidence: 59%
“…The second conclusion of Saville, Miller and Brumbelow (2016) is that, like other ISRSs, Envision does not allow for adjustments to the weightings to reflect local sustainability needs.…”
Section: There Is No Weighting Of Criteria Based Upon Local Needsmentioning
confidence: 99%
“…ANNs have also been used to identify maps of the probabilities of drought occurrences in Portugal [43], while a multi-objective optimization model has been applied for rural water supply systems in Cuiabá, Brazil [44]. In other studies, the envision rating system was used to assess the sustainability of groundwater infrastructure to address concerns for water supply [45]. These studies can provide robust alternative ways to investigate the sustainability of projects and water management decisions, including water poverty for integrated planning and water resources management; however, this was outside the scope of the present research and, therefore, awaits another independent study.…”
Section: Issues and Challenges Of Wpi Used To Assess Water Stress Andmentioning
confidence: 99%